The measurement of market concentration in Irish banking - Kinsella, R. P. (Statistical and Social Inquiry Society of Ireland, 1981)
This paper analyses the market structure of Irish banking, with particular reference to market concentration. While it is generally recognised that the Irish banking system is relatively highly concentrated there have been few attempts to give empirical precision to this feature. I begin this paper by examining changes in the number of licensed banks since 1960. We next consider what is, perhaps, the most widely used measure of market concentration, the concentration ratio. While useful as a starting point, the concentration ratio has important limitations as a measure of market structure. Hence, we look at measures of relative concentration ? that is, measures which take account of changes in output among all licensed banks as opposed to just the largest banks. The Herfindahl-Index, which has been widely used in US studies of market structure in recent years, is discussed in some detail. Measures of inequality with respect to the distribution of output among all banks, including Lorenz curves and the related Gini Coefficient, are also discussed. Finally, changes in bank turnover (that is, changes in rankings over time) and in market shares are examined. The main features of the market structure of Irish banking, as reflected in these various measures, are then summarised.
Read before the Society, 12 February 1981
Keywords: Irish banking; Market concentration ratio; Irish financial services sector; 314.15